Two precursors of melanin-concentrating hormone: DNA sequence analysis and in situ immunochemical localization. - Minth, C D (1989)
Two precursors to Chinook salmon (Oncorhynchus tshawytscha) melanin-concentrating hormone, an important factor in teleosts involved in the control of skin pigmentation and stress responsiveness, have been identified from DNA sequence analysis. Both precursors encode proteins of 132 amino acids and they share 107/132 amino acid identities. The biologically active 17-residue peptide is located at the C terminus of both precursors and can be liberated by proteolytic cleavage following two adjacent arginine residues. Additional putative proteolytic processing sites are located within the two precursors. Northern analysis demonstrated an intense hybridization signal of 750 nucleotides in the hypothalamus. Immunocytochemical studies as well as in situ hybridization analyses identify intensely staining cell bodies in the hypothalamus in the area of the lateral tuberal nucleus.